A New Species of Meliosma (Sabiaceae) from Southeastern Brazil and Notes on the Genus - Lombardi, Julio Antonio [UNESP] (Missouri Botanical Garden, 2009)
Meliosma chartacea Lombardi (Sabiaceae), a new species from southeastern Brazil, is described from Minas Gerais and Espirito Santo. It is characterized by its entire internal petals, very short petiole (generally less than I cm), brochidodromous venation, and entire leaf margin. A key to determine the species from southeastern Brazil is presented. Lectotypes and new synonyms are proposed for formerly described Brazilian species: M. sellowii Urban and M. itatiaiae Urban.
Keywords: Brazil; IUCN Red List; Meliosma; Sabiaceae; South America